Vascular manifestations of syndromic aortopathies: role of current and emerging imaging techniques. Issue 12 (December 2015) - Westerland, O.; Frigiola, A.; Robert, L.; Shaw, A.; Blakeway, L.; Katsanos, K.; Kiesewetter, C.; Chung, N.; Karunanithy, N.
Abstract : Patients with connective tissue diseases such as Marfan's syndrome, Loeys–Dietz syndrome, and vascular Ehlers–Danlos syndrome comprise a small but important group of patients who present early with acute aortic syndrome comprising aneurysmal dilation, rupture, or aortic dissection. Cardiovascular pathologies are an important yet treatable cause of morbidity and mortality in these patients. Imaging plays an important role in initial diagnosis, surveillance, and identification of complications. Furthermore, these patients are prone to developing complications in other vascular territories. Effective screening and surveillance will allow early diagnosis and elective treatment thus reducing the morbidity and mortality associated with presentation with acute complications. In this article, we will provide an overview of the role of magnetic resonance and computed tomography angiography in the management of syndromic aortopathies.